Prescrição da pretensão executória: uma discussão sobre o trânsito em julgado da sentença condenatória para acusação - Gurpilhares, Giovana Gleice Gomes dos Santos (2007)
This work is focused on the initial term of the executory pretension prescription, due to the article 112, inc. I, part I of the Penal Code, which establishes the day the condemnatory sentence is passed on, for accusation. This term, several times prevents the State from fully executing the penalty imposed, due to the extinction of the punishability by prescription. This happens, for the prescriptional term starts with the definite sentence for the accusation, but this can only execute the penalty after the sentence becomes definite for both parties. Aiming to understand the rate and show the consequences of this norm, the origin and evolution of the right of the State to punish, the purposes of the penalty, the extinctive causes of the punishability anticipated in the Penal Code, the origin and evolution of the prescription in the compared law, the compared law on the subject and some constitutional principles are approached. Besides that, some criminal processes and bills that direct or indirectly deal with this issue were analyzed. It was verified that the situation arisen in function of this initial term represents a very high disproportion between the parties, since in the conflict between the jus puniendi pertaining the State and the jus libertatis pertaining the defendant, a great disadvantage of the first one in relation to the second occurs. The constitutional principle of equality is flagrantly violated, for art. 5 of the Federal Constitution of 1988 declares that all people are equal under the law, with no distinction of any nature and this is also applied to the State, as office holder of the jus puniendi. In the case herein discussed the handling is unequal, with no justification for that